NoSQL For Dummies. - Fowler, Adam (--For dummies., 2015)
Featuring specific evaluation criteria for NoSQL databases, along with a look into the pros and cons of the most popular options, this book provides the fastest and easiest way to dive into the details of this technology. You'll gain an understanding of how to use NoSQL databases for mission-critical enterprise architectures and projects, and real-world examples reinforce the primary points to create an action-oriented resource for IT pros. You will learn the basic tenets of NoSQL databases and why they have come to the forefront as data has outpaced the capabilities of relational databases; discover major players among NoSQL databases, including Cassandra, MongoDB, MarkLogic, Neo4J, and others; get an in-depth look at the benefits and disadvantages of the wide variety of NoSQL database options; explore the needs of your organization as they relate to the capabilities of specific NoSQL databases. --